Barriers and facilitators to adherence to anti-diabetic medications: Ethiopian patients' perspectives - Bruck M. Habte; Tedla Kebede; Teferi G. Fenta; Heather Boon (AOSIS, 2017)
Background: Little is known about the experiences of Ethiopian patients with type 2 diabetes related to adherence to their anti-diabetic medications. This may limit attempts to develop and implement patient-centred approaches that consider Ethiopian contexts. Objectives: To conduct an exploratory study with a focus on identifying barriers and facilitators to anti-diabetic medications adherence in Ethiopian patients with type 2 diabetes. Methods: Qualitative methods were used to conduct semi-structured interviews with 39 purposively selected participants attending clinic in three public hospitals in central Ethiopia. Open coding was used to analyse the data to identify key themes. Results: A number of factors were identified as barriers and facilitators to participants' adherence to their anti-diabetic medications. The most common factors were perceptions related to their illness including symptoms, consequences and curability; perceptions of medications including safety concerns, convenience and their necessity; religious healing practices and beliefs; perceptions about and experiences with their healthcare providers and the healthcare system including the availability of medications and diabetes education; and finally perceived self-efficacy and social support. Conclusions: The findings of this study provide guidance to strengthen diabetes education programmes so that they reflect local patient contexts focusing among other things on the illness itself and the anti-diabetic medications.